The P-glycoprotein Inhibitor GF120918 Modulates Ca(2+)-Dependent Processes and Lipid Metabolism in Toxoplasma Gondii - Bottova, Iveta (Public Library of Science, 2010)

(untitled)
Up-regulation of the membrane-bound efflux pump P-glycoprotein (P-gp) is associated with the phenomenon of multidrug-resistance in pathogenic organisms, including protozoan parasites. In addition, P-gp plays a role in normal physiological processes, however our understanding of these P-gp functions remains limited. In this study we investigated the effects of the P-gp inhibitor GF120918 in Toxoplasma gondii, a model apicomplexan parasite and an important human pathogen. We found that GF120918 treatment severely inhibited parasite invasion and replication. Further analyses of the molecular mechanisms involved revealed that the P-gp inhibitor modulated parasite motility, microneme secretion and egress from the host cell, all cellular processes known to depend on Ca(2+) signaling in the parasite. In support of a potential role of P-gp in Ca(2+)-mediated processes, immunoelectron and fluorescence microscopy showed that T. gondii P-gp was localized in acidocalcisomes, the major Ca(2+) storage in the parasite, at the plasma membrane, and in the intravacuolar tubular network. In addition, metabolic labeling of extracellular parasites revealed that inhibition or down-regulation of T. gondii P-gp resulted in aberrant lipid synthesis. These results suggest a crucial role of T. gondii P-gp in essential processes of the parasite biology and further validate the potential of P-gp activity as a target for drug development.